Smurf1 Facilitates Oxidative Stress and Fibrosis of Ligamentum Flavum by Promoting Nrf2 Ubiquitination and Degradation - Yifei Gu; Jinquan Hu; Chen Wang; Min Qi; Yu Chen; Wenchao Yu; Zhanchao Wang; Xinwei Wang; Wen Yuan (Hindawi Limited, 2023)
Lumbar spinal stenosis (LSS), which can lead to irreversible neurologic damage and functional disability, is characterized by hypertrophy and fibrosis in the ligamentum flavum (LF). However, the underlying mechanism is still unclear. In the current study, the effect of Smurf1, a kind of E3 ubiquitin ligase, in promoting the fibrosis and oxidative stress of LF was investigated, and its underlying mechanism was explored. The expression of oxidative stress and fibrosis-related markers was assessed in the tissue of lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH). Next, the expression of the top 10 E3 ubiquitin ligases, obtained from Gene Expression Omnibus (GEO) dataset GSE113212, was assessed in LDH and LSS, and confirmed that Smurf1 expression was markedly upregulated in the LSS group. Furthermore, Smurf1 overexpression promotes the fibrosis and oxidative stress of LF cells. Subsequently, NRF2, an important transcription factor for oxidative stress and fibrosis, was predicted to be a target of Smurf1. Mechanistically, Smurf1 directly interacts with Nrf2 and accelerates Nrf2 ubiquitination and degradation. In conclusion, the current study suggests that Smurf1 facilitated the fibrosis and oxidative stress of LF and induced the development of LSS by promoting Nrf2 ubiquitination and degradation.